Transient Voltage Analysis for Dynamic Positioning Closed Bus Electrical System on Ship in Laboratory Scale - Sardono Sarwito; Eddy Setyo Koenhardono; A.A Masroeri; Indra Ranu Kusuma; Mochamad Nur Ichwan (International Journal of Marine Engineering Innovation and Research, 2019)
Ships equipped with a dynamic positioning system has a more number of thuster than ships that are not equipped with a dynamic positioning system. The addition of this thruster resulted in a significant increase in electrical loads so that the power plant will be added to the vessel. Dynamic positioning is a system used to support offshore vessel work consisting of a collection of equipment and control systems that work simultaneously to maintain the position of a vessel in accordance with which has been input into the system. Installation of the dynamic positioning system on the vessel affects the electrical system of the vessel. In the operation of electrical system on the vessel found the disturbances that arise one of them is transient interference that causes the change of voltage and frequency value in a short time. A Transient voltage occurs within a few seconds where the system conditions are unstable. The research was conducted in a laboratory scale by modeled a series of vessels that have the system with existing laboratory equipment where transient interference occurred due to the starting motor so that it is done Analysis of the magnitude of the voltage and frequency in the specified scenario as well as finding a solution to correct emerging interference that exceeds the standard. In the experiments made some configuration changes and obtained the result that the configuration of Split Plant 1 generator thruster has good system stability capable of achieving a stable condition with a loading of 50%. As for the loading of 60% stability of the system is unstable and can be improved again with the addition of capacitor.